FTA Highlight No.4 – Forest and Landscape Restoration - Guariguata, Manuel R.; Atmadja, S.; Baral, H.; Boissiere, M.; Brady, M.A.; Chomba, S.; Cronkleton, P.; Djoudi, H.; Duchelle, Amy E.; Duguma, L.A.; Elias, M.; Gitz, V.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Forest and landscape restoration (FLR) provides a framework for implementing restorative interventions that collectively address major environmental challenges such as soil and land degradation, biodiversity loss, water scarcity, lack of sustainable rural livelihoods, and climate change mitigation and adaptation. Restorative interventions can take many forms, which vary in cost, trajectory and specific economic and social outcomes; likewise, their benefits accrue to various actors and stakeholders. Over the last decade, the CGIAR Program on Forests, Trees and Agroforestry (FTA) has undertaken innovative basic and applied research across different scientific disciplines on the multiple dimensions of FLR for improving policy and practice and facilitating the uptake of new knowledge, tools and approaches — both from the top down and the bottom up. This publication presents key FTA outputs on forest and landscape restoration from 2011 to 2021. Many of them have contributed to informing the implementation of FLR interventions at multiple scales of work. These outputs are presented according to five broad areas of influence: (1) contributions to restoration science; (2) contributions to global narratives and discourses; (3) contributions to policy and governance; (4) focusing on actors on the ground; and (5) contributions to national and international dialogues. The last section (6) discusses ways to move forward.